Measurements of the nuclear modification factor for jets in Pb+Pb collisions at √sNN=2.76 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Dunford, Monica; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; Lang, Valerie; Meier, Karlheinz; et al. (Physical review letters, 2015)
Measurements of inclusive jet production are performed in pp and Pb+Pb collisions at √sNN=2.76  TeV with the ATLAS detector at the LHC, corresponding to integrated luminosities of 4.0 and 0.14  nb−1, respectively. The jets are identified with the anti-kt algorithm with R=0.4, and the spectra are measured over the kinematic range of jet transverse momentum 32<pT<500  GeV and absolute rapidity |y|<2.1 and as a function of collision centrality. The nuclear modification factor RAA is evaluated, and jets are found to be suppressed by approximately a factor of 2 in central collisions compared to pp collisions. The RAA shows a slight increase with pT and no significant variation with rapidity.